"PENGARUH LAMA PERENDAMAN DALAM LARUTAN GULA TERHADAP MUTU KERIPIK PISANG TONGKA LANGIT (Musa troglodytarum L.)" - Siallagan, Curnia Dumasari; Tetelepta, G; Laawalata, V.N. (Jurnal Sains dan Teknologi Pangan, 2022)
CURNIA DUMASARI SIALLAGAN. The Effect of Soaking Time in Sugar Solution on the Quality of Tongka Langit Banana Chips Supervised by G. TETELEPTA and V. N. LAWALATA Tongka Langit banana is a local commodity native to Maluku which has high nutritional content and health benefits. Tongka Langit banana can be processed into chips. Tongka Langit banana chips are one of the processed products of Tongka Langit bananas that need to be considered for the level of crispness. To maintain the crispness of Tongka Langit banana chips, they need to be soaked in a sugar solution. The purpose of this study was to analyze and determine the length of time soaking in a sugar solution to produce the best quality chips. This study used a completely randomized design (CRD) with treatment duration of immersion in sugar solution 5, 10, 15 and without immersion. The results showed that the treatment of immersion in a sugar solution for 5 minutes was the best result with the chemical characteristics of water content 5.24%, ash content 1.81%, fat content 48%, protein content 1.86%, carbohydrate content 43.10%, Vitamin C content is 0.21% and based on hedonic organoleptic test, the color is slightly like (2.8), the taste is like (3.1), the texture is like (3.35), while the hedonic quality shows a yellow color (2.95). , slightly sweet taste (2.35) and crunchy texture (3.3).Keywords: Tongka Langit Banana, Soaking Time, Sugar, Chips